Mental health challenges and HIV status disclosure among children and adolescents living with HIV in Eastern Uganda - Joseph Kirabira; Godfrey Zari Rukundo; Letizia Atim; Celestino Obua; Edith K. Wakida; Christine Etoko Atala; Naume Etoko Akello; Helen Byakwaga; Scholastic Ashaba; Brian C. Zanoni (Scientific Reports, 2025)
Worldwide the prevalence of children and adolescents on antiretroviral therapy is increasing with the advancement in pediatric HIV care. However, this presents unique challenges associated with HIV status disclosure to the child or the adolescent without negatively affecting treatment outcomes. The primary objective of the study was to determine the prevalence of mental health challenges and their association with HIV status disclosure among children and adolescents seeking care at three pediatric HIV clinics in Eastern Uganda. This prospective cross-sectional study was conducted among children and adolescents aged 8–17 years. Disclosure was assessed using an adapted United States Agency for International Development -Academic Model Providing Access to Healthcare (AMPATH) disclosure questionnaire. Mental health outcomes (major depression, suicidality, generalized anxiety and alcohol use disorder) were evaluated using the Mini International Neuropsychiatric Interview (MINI-KID) questionnaire, stigma using the Internalized AIDS-Related Stigma Scale and social support using the Multidimensional Scale of Perceived Social Support. Prevalence of disclosure was determined as a proportion of participants in the study group who screened positive for disclosure as per the AMPATH disclosure questionnaire. Factors associated with mental health conditions were determined by running bi-variable and multivariable logistic regression models. Among the 326 children and adolescents enrolled, 23.3% (n = 76) had at least one mental health challenge (MHC). The prevalence of major depression was 14.1%, suicidality, 12.8%, generalized anxiety disorder, 8.59% and alcohol use disorder was 1.2%. MHCs were more common among children and adolescents living with HIV who had been disclosed of their HIV status. HIV status disclosure was a risk factor for both major depression (adjusted odds ratio (aOR) = 2.98, p = 0.018) and suicidality (aOR = 2.72, p = 0.031) but not generalized anxiety disorder. Older age (13–17 years) was a risk factor for major depression (aOR = 2.52, 95%, p = 0.001), while maternal caregiving (aOR = 0.42, p = 0.026) was protective. Generalized anxiety disorder (aOR = 7.44, p < 0.001) was a strong risk factor for suicidality while high perceived social support (aOR = 0.39, p = 0.024) was protective. Education level above primary (aOR = 2.80, p = 0.030) and internalized stigma (aOR = 1.67, p = 0.041) were risk factors for generalized anxiety disorder. Children and adolescents face unique mental health challenges associated with HIV status disclosure which calls for sociocultural appropriate interventions to bridge this gap.
Keywords: HIV; Disclosure; Mental health children and adolescents; Depression; Anxiety; Suicidality